An Unusual Presentation of Tyrosinemia Type 1 in a Pediatric Patient: Case Report and Comprehensive Review - Mahsa Rouhafshari; Mohammad Hadi Imanieh; Mahdi Khazaei; Zahra Radaei; Hamide Barzegar (Clinical Case Reports)
ABSTRACT Tyrosinemia type 1 often manifests with liver, renal, or peripheral neuropathy disorders. Before therapies like nitisinone, management was limited to dietary modifications and liver transplantation. We present a 19‐month‐old girl who developed respiratory distress requiring intubation, with abnormal laboratory findings, including liver function tests. Further work‐up, including succinylacetone testing, confirmed tyrosinemia. She responded remarkably to nitisinone treatment.